The oxidative-stress-senescence axis in keratoconus: new insights into corneal degeneration - Passaro, Maria Laura; Rinaldi, Michele; Morgera, Valentina; Feola, Antonia; Romano, Vito; Troisi, Mario; Strianese, Diego; Piscopo, Raffaele; Messina, Samantha; Romano, Antonella; Porcellini, Antonio; Pezone, Antonio; et al. (Frontiers in Molecular Biosciences, 2025)
Keratoconus is a bilateral and asymmetric degenerative eye disease that causes corneal thinning and bowing, leading to irregular astigmatism and vision loss. Although environmental and genetic factors contribute to the disease’s development, the exact cause and underlying pathological mechanism remain unknown. In this review, we comprehensively explore the latest pathophysiological mechanisms of keratoconus, focusing on oxidative damage and inflammation. Senescence emerges as a key driver of keratoconus pathogenesis. Understanding these common elements enhances our understanding of the disease and paves the way for innovative therapeutic approaches to keratoconus.